2008
DOI: 10.1080/03650340701817014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of straw mulching, irrigation and fertilizer nitrogen levels on soil hydrothermal regime, water use and yield of hybrid chilli

Abstract: In northern India, chilli is transplanted in the hot and dry months of February and March when the crop depends upon irrigation water for canopy establishment. Hybrid chilli may require more irrigation water and fertilizer N due to its higher yield potential but the problem of the depleting groundwater table in the region necessitates developing a technique for reducing water requirement. Rice residue mulching can lower soil temperature and reduce evaporation losses from soil. An experiment was conducted on sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
4
8
0
Order By: Relevance
“…2 that top 0.15-m soil layer in M 6 plots retained 0.8 to 1.7% more moisture (in absolute terms) than M 0 plots throughout the growing season in the I 2.0 regime in the loamy sand soil during 2009-2010. Higher soil moisture and moderation of soil temperature with residue mulching in the tropical and subtropical environments are in agreement with earlier reports (Aulakh and Sur 1999;Kar and Kumar 2007;Sekhon et al 2008). …”
Section: Soil Moisturesupporting
confidence: 92%
See 1 more Smart Citation
“…2 that top 0.15-m soil layer in M 6 plots retained 0.8 to 1.7% more moisture (in absolute terms) than M 0 plots throughout the growing season in the I 2.0 regime in the loamy sand soil during 2009-2010. Higher soil moisture and moderation of soil temperature with residue mulching in the tropical and subtropical environments are in agreement with earlier reports (Aulakh and Sur 1999;Kar and Kumar 2007;Sekhon et al 2008). …”
Section: Soil Moisturesupporting
confidence: 92%
“…As optimum soil temperature for potato is 15-20°C (Borah and Milthorpe 1963), the high maximum soil temperature in M 0 was detrimental for crop growth. Similar effects of residue mulching on soil temperature have been reported in this region (Singh et al 1988;Sekhon et al 2008).…”
Section: Resultssupporting
confidence: 74%
“…In the study by Najafabadi et al (2012), soil mulching with straw contributed to increased vitamin C content in garlic bulbs. On the contrary, Sekhon et al (2008) found significantly higher content of ascorbic acid in sweet pepper fruits cultivated in a control plot without mulch, compared to the plots with organic mulch. Gajc-Wolska et al (2005) found that sweet pepper fruits cultivated on mulch with straw contained significantly more vitamin C compared to those cultivated on polypropylene fibre mulch.…”
Section: Resultsmentioning
confidence: 66%
“…Changes in yields and nutrient content due to soil mulching were found by Samaila et al (2011a, b) in tomato fruits, by Najafabadi et al (2012) in garlic, by Olfati et al (2008) in carrot roots and by Sekhon at al. (2008) and Gajc-Wolska et al (2005) in sweet pepper.…”
Section: Introductionmentioning
confidence: 88%
“…The beneficial effects of this practice to improve crop yields at comparable irrigation regimes and saving of irrigation water and fertilizer nitrogen at comparable yields have been reported in several crops e.g. in forage maize, sugarcane, sunflower, soybean, potato and chillies by reducing the evaporation (E) component of the ET and acting as barrier to vapour flow, and moderating soil temperature (Arora et al 2011, Jalota et al 2007, Sekhon et al 2008, Yadvinder-Singh et al 2010b. The magnitude of yield gain in different crops ranged from 4 to 29% and saving of irrigation water from 7 to 40 cm.…”
Section: Crop Residues As Surface Mulch In Other Cropsmentioning
confidence: 99%